Mesoscale wind atlas of South Africa - Hagemann, Kilian (Department of Environmental and Geographical Science, 2014)
This thesis explores the utility of the MM5 regional climate model iii product big a detailed wind climatology for South Africa in the context of wind power applications. Given the background of limited available computational resources a sophisticated temporal subsetting algorithm is developed and applied. The goal here is to allow a high resolution 18 by 18km simulation to be carried out over only 365 days of historical records (20 March 1996 until 19 March 1997), yet ensure that it is possible to construct a reasonably accurate climatology from such a short time period because it represents the most typical year available. Throughout the research the modelâs sensitivity towards different boundary layer and cwnulus parametrisations as well as observational and grid nudging is investigated in depth. New error metrics are specifically designed and applied based on 17 reliable lOni weather stations around the country with the specific purpose of evaluating model skill with respect to the wind patterns that are important for wind turbines. An optimal model configuration is established by using the Pleim Xiu land surface scheme coupled with the Atmospheric Convective Model for the planetary boundary layer, in addition to the Kain Fiitsch II cumulus parametrisation and observational wind nudging. The model is then integrated at 18km for the entire country and the results validated in detail. It is found that average wind speeds are within 0.2 + 0.7ms (68% confidence interval) and that the daily cycle, which constitutes the largest part of the observed variance, is predicted to within 18% + 20% of amplitude and lii of timing at coastal sites.